The power of hydropeaking: Trade-offs between flexible hydropower and river ecosystem services in Europe - Venus, Terese E.; Ola, Oreoluwa; Alp, Maria; Bätz, Nico; Bejarano, Maria Dolores; Boavida, Isabel; Bruno, Maria Cristina; Casas-Mulet, Roser; Carolli, Mauro; Chiogna, Gabriele; Gosselin, Marie Pierre; Halleraker, Jo H.; et al. (Ecological Economics, 2025)
The operational practice of “hydropeaking” allows hydropower plants to cover peaks and deficits in energy demand, but it also impacts river ecosystems. The assessment of hydropeaking impacts plays an important role in safeguarding ecosystem services, but is challenging due to the relative importance of impacts at different sites. To compare impacts in hydropeaking rivers, we elicit expert judgment on the relative impacts of hydropeaking on river ecosystem services. Using the best-worst scaling (BWS) method, we compare the impact on the three categories of river ecosystem services (provisioning, regulating and cultural). Our respondents include 98 hydropower experts. Our analysis accounted for individual heterogeneity to assess how perceptions vary across regions, attitudes and representative river characteristics. We find trade-offs between provisioning and regulating services at the regional and local levels, which represents a key issue in dealing with climate change and ecosystem degradation. The best-affected services were water for power generation, raw materials, water for industrial activities and water for irrigation. The worst-affected services were fisheries and aquaculture, maintenance of population and habitat, and wild animals. Our results have implications for the safeguarding of river ecosystem services and the design of regulatory and incentive schemes for mitigation.
CRIS-Team Scopus Importer:2025-03-28
Keywords: Best-worst scaling; Biodiversity; Choice experiment; Ecological compensation; Ecosystem services; Hydropower